PENGARUH TINGKAT PENDIDIKAN, PEMAHAMAN AKUNTANSI DAN PERSEPSI PELAKU UMKM TERHADAP IMPLEMENTASI SAK EMKM PADA LAPORAN KEUANGAN UMKM DI KOTA MALANG - Ailansi Rambu Sedu Oyi; Syamsul Bahri; Zainudin Zainudin (Bajang Institute, 2023)
Micro, small and medium enterprises (MSMEs) play an important role in the economy in Indonesia. However, it has problems in recording financial statements. The government has ratified a financial reporting standard for MSMEs, namely SAK EMKM which aims to provide convenience for small and medium scale business entities in carrying out financial reporting. This study aims to examine the effect of educational level, understanding of accounting and perceptions of MSME actors on the implementation of SAK EMKM. The object of this research is the owners and employees of UMKM in the food sector in Malang City. Questionnaire as a data collection tool distributed to respondents with a sample of 80 respondents, was collected using the survey method with the sampling technique that is purposive sampling. The tool used to analyze the relationship between variables in this study was the application of the SPSS version 22 program. The results of this study indicated that partially the level of education and understanding of accounting had an effect on the implementation of SAK EMKM on the financial statements of MSMEs in Malang City, while the perceptions of MSME actors had no effect on implementation. SAK EMKM on MSME financial reports in Malang City. Simultaneously the level of education, understanding of accounting and perceptions of MSME actors influence the implementation of SAK EMKM.